2021
DOI: 10.3389/fpls.2021.790898
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocessed Wheat Ingredients: Characterization, Bioaccessibility of Phenolic Compounds, and Bioactivity During in vitro Digestion

Abstract: To enlarge the applications of whole wheat grain (WWG) and wheat bran (WB) as functional ingredients in foodstuffs that can promote human health, researchers have explored bioprocessing approaches to improve the bioaccessibility of phenolic compounds from these food matrices and, subsequently, their biological effects. The objective of this study was to compare the composition in nutrients, anti-nutrients, and bioactive compounds of WWG and WB, and their respective bioprocessed products: sprouted wheat (GERM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 67 publications
5
30
1
Order By: Relevance
“…Overall, the WB LP phenolic extracts modestly inhibited IL-1β, IL-6 secretion, and strongly the TNF-α levels ( p < 0.05), whereas they stimulate IL-10 secretion ( p < 0.05)—an anti-inflammatory cytokine able to inhibit the synthesis of proinflammatory cytokines in macrophages. Our results are in line with previous studies providing evidence of the anti-inflammatory effects of wheat phenolic compounds in LPS-induced RAW 264.7 macrophages [ 22 , 23 , 48 ]. Particularly, WB polyphenols have demonstrated modulatory actions, inhibiting the production of pro-inflammatory cytokines TNF-α and IL-6 in LPS-induced RAW264.7 macrophages.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the WB LP phenolic extracts modestly inhibited IL-1β, IL-6 secretion, and strongly the TNF-α levels ( p < 0.05), whereas they stimulate IL-10 secretion ( p < 0.05)—an anti-inflammatory cytokine able to inhibit the synthesis of proinflammatory cytokines in macrophages. Our results are in line with previous studies providing evidence of the anti-inflammatory effects of wheat phenolic compounds in LPS-induced RAW 264.7 macrophages [ 22 , 23 , 48 ]. Particularly, WB polyphenols have demonstrated modulatory actions, inhibiting the production of pro-inflammatory cytokines TNF-α and IL-6 in LPS-induced RAW264.7 macrophages.…”
Section: Resultssupporting
confidence: 93%
“…The TSC values observed were lower than those reported previously by other authors in grains and brans [ 20 , 48 ]. TSC variation could be attributed to variety, cultivation conditions and, in the specific case of brans, to the milling technique used for its separation, which determines the amount of starch attached to the aleurone layer after bran separation.…”
Section: Resultscontrasting
confidence: 86%
“…The increase in the amount of extractable phenolics in digested germinated seeds may be the result of digestive enzymes and bile salts acting on the modified spelt seed matrix and facilitating the release of bound phenolics into the digestive juice [ 16 ]. Furthermore, the transition from an acidic to an alkaline environment leads to deprotonation of hydroxyl moieties of aromatic rings, which may have contributed to the increased extractable TPC of digested germinated seeds [ 17 ]. A possible reason may also be the structure of germinated seeds, since starch in germinated seeds is generally more digestible due to the enzymatically modified structure of starch granules, thin cell walls and readily available mono- and disaccharides.…”
Section: Resultsmentioning
confidence: 99%
“…In general, p -coumaric and trans -ferulic acids showed the highest biostability, while p -hydroxybenzoic acid showed the lowest biostability. Tomé-Sánchez et al [ 17 ] also reported that ferulic acid derivatives of barley and wheat sprouts have high stability to digestion conditions. Interestingly, the lowest biostability of p -hydroxybenzoic acid was found in “enzymatic treated + fermented” seeds; it was almost 10-fold lower than in raw seeds.…”
Section: Resultsmentioning
confidence: 99%
“…TSPCs were analyzed according to Pico et al [ 21 ] with slight modifications [ 22 ]. Briefly, 50–100 mg of the milled sample containing 1 mL of 80% methanol in 0.1% formic acid were incubated in a Thermomixer at 30 °C and 2000 rpm for 15 min (Eppendorf AG, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%